Answer:
45
Step-by-step explanation:
Replace everything in the equation that has a x to -3:
f(-3)=3(-3)^2-4(-3)+6
Square the -3:
f(-3)=3(9)-4(-3)+6
Multiply/Distribute
f(-3)=27+12+6
Add:
f(-3)=45
Hope this helps!
Answer:
f(x) = 45
Step-by-step explanation:
f (x) = 3x^2 − 4x + 6 find f (−3)
Replace the variable x with −3 in the expression.
f (−3) = 3(−3)^2 − 4 ⋅ −3 + 6
Simplify 3(−3)^2 − 4 ⋅ −3 + 6
Remove parentheses.
3(−3)^2 − 4 ⋅ −3 + 6
Raise −3 to the power of 2.
3 ⋅ 9 − 4 ⋅ −3 + 6
Multiply 3 by 9.
27 − 4 ⋅ −3 + 6
Multiply −4 by −3.
27 + 12 + 6
Simplify by adding numbers.
Add 27 and 12.
39 + 6
Add 39 and 6.
45